2018
DOI: 10.1021/acs.langmuir.8b03727
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Pickering Emulsifier Performance of Anisotropic Cross-Linked Block Copolymer Worms: Effect of Aspect Ratio on Emulsion Stability in the Presence of Surfactant

Abstract: Reversible addition-fragmentation chain transfer (RAFT)-mediated polymerization-induced self-assembly (PISA) is used to prepare epoxy-functional PGMA48-P(HPMA90-stat-GlyMA15) diblock copolymer worms, where GMA, HPMA and GlyMA denote glycerol monomethacrylate, 2hydroxypropyl methacrylate and glycidyl methacrylate, respectively and the subscripts indicate the mean degrees of polymerization. The epoxy groups on the GlyMA residues were ring-opened using 2aminopropyltriethoxysilane (APTES) in order to cross-link th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 82 publications
0
40
0
3
Order By: Relevance
“…According to the literature, high-shear homogenization of diblock copolymer nano-objects can cause in situ dissociation in some cases, which leads to the formation of emulsion droplets stabilized by individual diblock copolymer chains acting as a polymeric surfactant. 52,53,55,75 Moreover, such instances typically involve PHPMA-core nanoparticles, albeit those prepared via aqueous PISA formulations rather than the present non-aqueous formulation. 52,53,55 Fortunately, whether such nano-object dissociation actually occurs in practice can be assessed by determining the variation in mean droplet diameter with copolymer concentration.…”
Section: Psma9-phpma50 Diblock Copolymer Spheres As Putative Pickering Emulsifiersmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, high-shear homogenization of diblock copolymer nano-objects can cause in situ dissociation in some cases, which leads to the formation of emulsion droplets stabilized by individual diblock copolymer chains acting as a polymeric surfactant. 52,53,55,75 Moreover, such instances typically involve PHPMA-core nanoparticles, albeit those prepared via aqueous PISA formulations rather than the present non-aqueous formulation. 52,53,55 Fortunately, whether such nano-object dissociation actually occurs in practice can be assessed by determining the variation in mean droplet diameter with copolymer concentration.…”
Section: Psma9-phpma50 Diblock Copolymer Spheres As Putative Pickering Emulsifiersmentioning
confidence: 99%
“…51 Since 2012, various types of diblock copolymer nano-objects have been evaluated as Pickering emulsifiers. [52][53][54][55] For example, hydrophilic diblock copolymer nanoparticles prepared via aqueous PISA enable the formation of oil-in-water (o/w) Pickering emulsions. [53][54][55] In contrast, hydrophobic nanoparticles prepared in non-polar solvents such as n-alkanes or mineral oil favour the formation of water-in-oil (w/o) emulsions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…71,86,93,94 In contrast, Thompson and coworkers reported essentially no change in the mean droplet diameter with copolymer concentration when using linear PGMA 45 -PHPMA 200 vesicles, which is consistent with the in situ break-up of these more delicate nano-objects during high-shear homogenization. 71,81,92 TEM studies of the dried emulsion droplets (see Fig. 6a) confirmed that linear PGMA 41 -PHBMA 110 vesicles do indeed remain intact after high-shear homogenization.…”
Section: Polymer Chemistrymentioning
confidence: 68%
“…Preparation of Pickering emulsions using PGMA-PHBMA vesicles RAFT-mediated PISA enables the design of a wide range of surface-active block copolymer nanoparticles that can stabilize either oil 42,71,[81][82][83] or water droplets, [84][85][86][87] as summarized in a recent review. 88 Particular attention has been paid to vesicles since they were the initial diblock copolymer nanoparticles to be utilized as Pickering emulsifiers.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%